EFFECT OF MORNING AND EVENING RAMIPRIL TAKING ON AMBULATORY BLOOD PRESSURE PROFILE IN PATIENTS WITH ARTERIAL HYPERTENSION - V. M. Gorbunov; E. J. Fedorova; A. D. Deev; E. V. Platonova; O. J. Isaikina (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To compare antihypertensive effect of ramipril monotherapy at morning and evening taking. Material and methods. 22 patients (10 men, 12 women; aged 62,1±1,9 y.o.) with arterial hypertension of 1-2 stage were involved into the open randomized crossover study. Patients were randomized into 2 groups depending on ramipril taking time (morning or evening). Ambulatory blood pressure (BP) monitoring (ABPM) was performed. Patients of both groups were comparable in basic clinical characteristics and initial ABPM indices. Analysis of peak and phase characteristics of 24 hour BP profile was used as well as standard evaluation. Treatment duration was 3 weeks. Ramipril dose titration was made in 1,5 weeks. The average daily dose of ramipril was 6,1 mg in the morning taking, and 5,0 mg in the evening taking. Results. 20 patients finished study completely. 24 hour initial level of systolic (SBP) and diastolic BP (DBP) was 141,5±1,6/85,3±1,1 mm Hg. After ramipril monotherapy with evening taking BP reduced to 132,6±1,6/79,8±1,1 mm Hg (p<0,001) and with morning taking – to 131,8±1,6/79,2±1,1 mm Hg (p<0,001). Evening ramipril taking led to significant improvement of 24 hour BP profile. Night SBP/DBP reduction became deeper from 7,7±1,2/11,5±1,3% to 12,5±1,2/19,1±1,3 % (p<0,01). Morning taking did not have significant influence on these indices. Ramipril did not result in clinically significant hypotension including night one. Conclusion. Evening ramipril taking is effective and safe. It can be recommended to patients with insufficient night BP dipping (non dippers).